Neuronal cytoplasmic inclusions in tau, TDP-43, and FUS molecular subtypes of frontotemporal lobar degeneration share similar spatial patterns - A. Armstrong, Richard (Folia Neuropathologica, 2017)
The ‘prion-like’ transfer of pathogenic proteins may play a role in the pathogenesis of frontotemporal lobar degeneration (FTLD). Propagation of such proteins along anatomical pathways may give rise to specific spatial patterns of the ‘signature’ neuronal cytoplasmic inclusions (NCI) characteristic of these disorders. Hence, the spatial patterns of the NCI were compared in three molecular subtypes of FTLD: (1) two variants of FTLD-tau, viz. corticobasal degeneration (CBD) and Pick’s disease (PiD), (2) FTLD with transactive response (TAR) DNA-binding protein 43(TDP-43)-immunoreactive inclusions (FTLD-TDP), and (3) FTLD with ‘fused in sarcoma’ (FUS)-immunoreactive inclusions (FTLD-FUS). Regardless of molecular pathology, the NCI in the frontal and temporal cortex were most frequently aggregated into clusters, the clusters being regularly distributed parallel to the pia mater. In a significant proportion of regions, the regularly distributed clusters were in the size range 400–800 μm, approximating the dimension of cell columns associated with the cortico-cortical pathways. Clusters of NCI were significantly larger in FTLD-tau compared with FTLD-TDP and FTLD-FUS. The data suggest that cortical NCI in different molecular subtypes of FTLD all share a similar spatial pattern in the frontal and temporal cortex consistent with a ‘prion-like’ spread of pathological proteins along anatomical pathways. However, a more selective group of neurons appears to be affected in FTLD-TDP and FTLD-FUS than in FTLD-tau.